Learning to Belong - PARKER, Lyn (Institutional Knowledge at Singapore Management University, 2010)
Educational efforts are being made around the country to enable minorities to feel they belong and to teach majorities that they should value the diversity of Indonesia. The cultural, linguistic and ethnic diversity of Indonesia is famed around the world and accepted within Indonesia. The national motto of ‘Unity in Diversity’ places diversity at the centre of the nation-state. But despite significant progress in democratisation, decentralisation and regional autonomy in post-Suharto Indonesia, old fears of federalism, separatism and disunity remain. Multiculturalism and pluralism are still often viewed with suspicion and paranoia is spread by extremists for their own ends.